Penggunaan Kontrasepsi di Kalangan Mahasiswa Universitas dalam Kelompok Etnis Yoruba di Nigeria: Peran Usia dan Gender - Tosin Emmanuel AKINDUYO (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
This study explored the influence of age and gender on contraceptive use among undergraduates in South-West Nigeria. The primary aim was to examine how contraceptive use among students is moderated by age and gender. The research employed a descriptive survey design, with a sample of 1,200 undergraduates (both male and female, aged 15 and above) selected through a multi-stage sampling method. Data were collected using a self-developed questionnaire, the